Australasian Conference on Information Systems 2018 2018
DOI: 10.5130/acis2018.bb
|View full text |Cite
|
Sign up to set email alerts
|

A review of information privacy laws and standards for secure digital ecosystems

Abstract: Information privacy is mainly concerned with the protection of personally identifiable information. Information privacy is an arduous task, in particular, in the context of complex adaptive and multi-party heterogeneous digital ecosystems. There is a need to identify and understand the relevant privacy laws and standards for designing the secure digital ecosystems. This paper presents the results of our information privacy research in digital ecosystems through the lens of local and international privacy regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In contrast, work specifically addressing digital ecosystems is thus far limited. Anwar et al [2] conducted a review of international laws, regulations, and standards to identify and sort aspects related to (1) the protection of individuals' privacy, (2) guarantees to be made about the processing, (3) measures to be taken for the handling of information, and (4) consequences for technical implementation. Kira et al [13] address the problem that digital ecosystems must comply with both competition policy and privacy law.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, work specifically addressing digital ecosystems is thus far limited. Anwar et al [2] conducted a review of international laws, regulations, and standards to identify and sort aspects related to (1) the protection of individuals' privacy, (2) guarantees to be made about the processing, (3) measures to be taken for the handling of information, and (4) consequences for technical implementation. Kira et al [13] address the problem that digital ecosystems must comply with both competition policy and privacy law.…”
Section: Related Workmentioning
confidence: 99%
“…In this scenario, studies, medical images, and electronic health records of the patient must be shared with the corresponding specialist to provide her with the tools for the diagnosis. Moreover, due to health data management laws [154], [155], the studies not only must be ensured by continuity schemes to fulfill NFRs but also must be stored for a large period.…”
Section: E Scenario Iv: Health Iot Data In Edge-fog-cloud Computing mentioning
confidence: 99%
“…However, they do not discuss which aspects of privacy should be covered by each dimension. Anwar et al (2018) found commonalities between privacy laws and standards, but noted differences in nature and scope which require further investigation. Martín et al (2014) highlighted a lack of technical privacy requirements and criticized disagreement between high-level privacy principles.…”
Section: Introductionmentioning
confidence: 93%
“…This paves the way for far more intrusive personal privacy violations, and its consequences are unforeseeable, endangering the privacy of individuals more than never before (Solove, 2002). Interestingly, more than 100 years after the Warren and Brandeis era and even after the 'cybernetic revolution' of the 1970s (Miller, 1969), the invention of the internet in the 1990s and today's multimedia world, lawyers, scientists and practitioners have still failed to reach an agreement on a blueprint for the principles of data protection (Anwar et al, 2018;Martín et al, 2014;Nissenbaum, 2015). One thing, however, is sure: What we can learn from former generations is to take invasion of privacy seriously (Barbas, 2012;Gavison 1992).…”
Section: The Right To Be Left Alonementioning
confidence: 99%